Accelerating progress an empowered, inclusive and equal Asia and the Pacific.
These elements include (i) rights and justice, (ii) norms and institutions, (iii) resources and capabilities, and (iv) participation and voice areas where governments, development partners, and the United Nations system can work with society more effectively. As a thematic report of the Asia Pacific Sustainable Development Goal Partnership for 2019 that reflects on the theme of the Asia Pacific Forum on Sustainable Development, it is designed to inform regional and global dialogue on sustainable development as well as national and regional implementation of the 2030 Agenda.